I Am Malala : The Girl Who Stood Up for Education and was Shot by the Taliban - Yousafzai, Malala; Lamb, Christina (Weidenfeld & Nicolson London, 2013)
When the Taliban took control of the Swat Valley in Pakistan, one girl spoke out. Malala Yousafzai refused to be silenced and fought for her right to an education. On Tuesday, October 9, 2012, when she was fifteen, she almost paid the ultimate price. She was shot in the head at point-blank range while riding the bus home from school, and few expected her to survive. Instead, Malala's miraculous recovery has taken her on an extraordinary journey from a remote valley in northern Pakistan to the halls of the United Nations in New York. At sixteen, she has become a global symbol of peaceful protest and the youngest nominee ever for the Nobel Peace Prize. This is the remarkable tale of a family uprooted by global terrorism, of the fight for girls' education, of a father who, himself a school owner, championed and encouraged his daughter to write and attend school, and of brave parents who have a fierce love for their daughter in a society that prizes sons. This story will make you believe in the power of one person's voice to inspire change in the world.-- Publisher information
Prologue : The Day My World Changed ; Part 1. Before the Taliban : A Daughter is Born ; My Father the Falcon ; Growing Up in a School ; The Village ; Why I Don't Wear Earrings and Pashtuns Don't Say Thank You ; Children of the Rubbish Mountain ; The Mufti Who Tried to Close Our School ; The Autumn of the Earthquake ; Part 2. The Valley of Death : Radio Mullah ; Toffees, Tennis Balls and the Buddhas of Swat ; The Clever Class ; The Bloody Square ; The Diary of Gul Makai ; A Funny Kind of Peace ; Leaving the Valley ; Part 3. Three Bullets, Three Girls : The Valley of Sorrows ; Praying to be Tall ; The Woman and the Sea ; A Private Talibanization ; Who is Malala ? ; Part 4. Between Life and Death : "God, I Entrust Her to You" ; Journey into the Unknown ; Part 5. A Second Life : "The Girl Shot in the Head, Birmingham" ; "They have Snatched Her Smile" ; Epilogue : One Child, One Teacher, One Book, One Pen... ; Glossary ; Important Events in Pakistan and Swat ; A Note on the Malala Fund
Keywords: Autobiography : Adolescent - Pakistan